Upaya Membentuk Motivasi Belajar Peserta Didik melalui Model Flipped Classroom dalam Pembelajaran PAI - Alaniah, Almas Sharfina; Soraya, Irma; Hamdani, Asep Saepul (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
The purpose of this study was to find out and analyze students' learning motivation through the flipped classroom model in PAI learning. This study uses a qualitative approach by uncovering and studying the application of the flipped classroom learning model in PAI learning. Data collection techniques were obtained through interviews and observations in order to gather information related to the implementation of the flipped classroom model. The research results explain that in the application of this learning model it can be carried out in different times and places between educators and students. This model prioritizes students to be more independent in learning. There are obstacles in the application of this learning, namely the difficulty of educators in monitoring students, students' weak memory, lack of support from parents, school facilities and infrastructure, and students' difficulties in understanding the lessons given. The efforts that can be made are to motivate students in overcoming obstacles from the flipped classroom learning model, namely refreshing, parenting counseling, innovation, and skill improvisation.